(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
The present paper attempts to study the bi-objective hospital site determination problem under fuzzy environment. In this paper, the concept of Tabu search is used for solving bi-objective facility location problem i.e. the most suitable hospital site to be searched out of the various possible sites nearest to the accidental prone areas so as to minimize the total transportation cost along with the transportation time using triangular fuzzy numbers. For this, we first search the hospital sites near accidental prone areas and then on the basis of that we obtain various optimal solutions with different transportation costs and times.